I Hear My Voice; Therefore I Spoke: The Sense of Agency Over Speech Is Enhanced by Hearing One's Own Voice. (August 2022) - Ohata, Ryu; Asai, Tomohisa; Imaizumi, Shu; Imamizu, Hiroshi
The subjective experience of causing an action is known as the sense of agency. Dysfunctional sense of agency over speech has been suggested as a cause of auditory hallucinations. However, agency over speech has not been extensively characterized in previous empirical studies. Here, we manipulated self-voice identity, an indicator of self, embedded in the acoustic quality of voice and examined implicit and explicit measures of the sense of agency. Experiment 1 ( N = 29 adults) demonstrated more compression of a perceived interval between action and outcome when participants heard their undistorted voices than their pitch-distorted voices. Experiment 2 ( N = 28 adults) revealed a strong top-down effect of self-voice identity: Specifically, the judgment of agency over speech was more resistant than the judgment of agency over hand/limb movement to low-level sensorimotor inconsistency. Our findings provide new insight into the sense of agency over speech and an informative perspective for understanding aberrant experience in auditory hallucinations.